Targeting overexpressed HSPA8 by halofuginone suppresses aberrant proliferation and invasion of rheumatoid arthritis fibroblast-like synoviocytes - Yuanyuan Tang; Han Wu; Ping Yan; Zhangxuan Yue; Zeyu Hu; Xunqi Liao; Yali Wang; Ye Lin; Liqing Li; Xiong Cai (Pharmacological Research)
Rheumatoid arthritis (RA) is a challenging autoimmune disorder characterized by fibroblast-like synoviocyte (FLS)-driven synovitis and joint destruction. Halofuginone (HF), a bioactive derivative of febrifugine isolated from the root of Dichroa febrifuga Lour., exhibits therapeutic potential in RA yet its molecular targets remain to be elucidated. In this study, we demonstrated that oral HF treatment (1.25 and 2.5 mg/kg, every other day) significantly inhibited disease progression of adjuvant-induced arthritis (AIA) in rats manifested by markedly less extent of synovial proliferation, cartilage destruction, and bone erosion. HF (0.1–0.8 μM) exerted dose-dependent inhibition on RA-FLS proliferation, invasion, and inflammatory response via targeting HSPA8 as confirmed by surface plasmon resonance (SPR) analysis showing direct binding (KD=3.877 μM). Notably, HSPA8 exhibited pronounced overexpression in AIA synovial tissue and RA-FLS versus controls. siRNA knockdown of HSPA8 significantly reduced RA-FLS proliferation, invasion, and inflammatory response, while adenoviral overexpression of HSPA8 exacerbated these phenotypes. Mechanistically, HF markedly reduced HSPA8 expression in the synovium of AIA rats and RA-FLS. These findings establish HSPA8 as a novel therapeutic target in RA and validate HF as its natural inhibitor, providing mechanistic insights for HSPA8-targeted RA therapies.